PERSEWAAN INTERNET DENGAN SISTEM ZMART BILLING PERSPEKTIF HUKUM ISLAM - Rahman Agustiana (Maliyah : Jurnal Hukum Bisnis Islam, 2016)
The role of internet cafes is very large as the digital divide. Through internet cafes, people can easily access the Internet without having to purchase hardware. Internet cafes services utilization in Islam is a form of contract ijara>h. The proliferation of internet cafes, of course, the greater the competition between businesses. Dian_net in operations using the system "zmart billing". Zmart Billing system is an application in the transaction using the username and password written on a piece of paper with the active period of 3 days. Zmart billing price discriminate students and the public. This difference is not a problem because there has been a mutual willingly among the perpetrators. Internet station with Zmart billing system in Dian_Net has qualified pillar rental contract according to Islamic law (contract ijara>h). Nevertheless, there are still users of Internet services in Dian_Net, especially new users, they do not know Zmart billing system for billing Zmart system is different from the other internet cafes surrounding environment.